Association of carbamylated high-density lipoprotein with coronary artery disease in type 2 diabetes mellitus: carbamylated high-density lipoprotein of patients promotes monocyte adhesion - Chen, Zhongli; Ding, Song; Wang, Yan Ping; Chen, Liang; Mao, Jing Yan; Yang, Ying; Sun, Jia Teng; Yang, Ke (Journal of translational medicine, 2020)
Increasing evidence showed that carbamylated lipoprotein accelerated atherosclerosis. However, whether such modification of high-density lipoprotein (HDL) particles alters in type 2 diabetes mellitus (T2DM) patients and facilitates vascular complications remains unclear. We aimed to investigate the alteration of the carbamylation in HDL among T2DM patients and clarify its potential role in atherogenesis. A total of 148 consecutive T2DM patients undergoning angiography and 40 age- and gender-matched control subjects were included. HDL was isolated from plasma samples, and the concentration of HDL carbamyl-lysine (HDL-CBL) was measured. Furthermore, the HDL from subjects and in-vitro carbamylated HDL (C-HDL) was incubated with endothelial cells and monocyte to endothelial cell adhesion. Adhesion molecule expression and signaling pathway were detected. Compared with the control group, the HDL-CBL level was remarkably increased in T2DM patients (6.13 ± 1.94 vs 12.00 ± 4.06 (ng/mg), P < 0.001). Of note, HDL-CBL demonstrated a more significant increase in T2DM patients with coronary artery disease (CAD) (n = 102) than those without CAD (n = 46) (12.75 ± 3.82 vs. 10.35 ± 4.11(ng/mg), P = 0.001). Multivariate logistic regression analysis demonstrated that higher HDL-CBL level was independently associated with a higher prevalence of CAD in diabetic patients after adjusting for established cofounders (adjusted odds ratio 1.174, 95% confidence Interval 1.045-1.319, p = 0.017). HDL from diabetic patients with CAD enhanced greater monocyte adhesion than that from the non-CAD or the control group (P < 0.001). Such pro-atherogenic capacity of diabetic HDL positively correlated with HDL-CBL level. Furthermore, in-vitro incubation of carbamylated HDL (C-HDL) with endothelial promoted monocyte to endothelial cell adhesion, induced upregulation of cell adhesion molecules expression, and activated NF-κB/p65 signaling in endothelial cells. Inhibiting carbamylation of HDL or NF-κB activation attenuated the monocyte to endothelial cell adhesion and cell surface adhesion molecules expression. Our study identified elevated carbamylation modification of HDL from T2DM patients, especially in those with concomitant CAD. We also evidenced that C-HDL enhanced monocyte to endothelial cell adhesion, indicating a potential pro-atherogenic role of C-HDL in atherosclerosis among T2DM patients. Trial registration https://register.clinicaltrials.gov , NCT04390711 Registered on 14 May 2020; Retrospectively registered.